474 Isolated pulmonary endocarditis. (17th January 2020) - Fernandez Valledor, A; Cepas Guillen, P; Izquierdo, M; Vidal, P; Pereda, D; Prat, S; Vidal, B; ,
Abstract: INTRODUCTION: Isolated pulmonary endocarditis is a rare entity, especially in patients without predisposing factors, being its current incidence less than 1% of the total cases of infectious endocarditis. This is due to the lower right heart pressures and a decrease of intravenous drug-consum, being most of the cases nowadays, related to congenital right-heart diseases or pacemakers and defibrillators implants. CLINICAL CASE: A 35 year-old man, tobacco smoker and intravenous cocaine consumer since he was 25, was admitted to our Emergency Department for fever up to 40ºC, cough and dyspnea started three days before admission. In the anamnesis he refereed intravenous consum of cocaine and sharing of syringes the last week. On physical examination he was tachycardic and signs of heart right failure were present such as jugular ingurgitation and peripheral edema. No murmurs were heard. No respiratory failure was detected at any time. Blood test analysis showed high levels of protein C reactive and leukocytosis. Blood cultures were positive for S. aureus (OXA-S) in the first 24h. Chest X-ray (image 1) showed a necrotizing bilateral pneumonia that was confirmed with the presence of cavitated images in the pulmonary CT (image 2). Antibiotic treatment was started with daptomicine + cloxaciline. With the suspicion of right endocarditis a transthoracic echocardiography was performed, showing the presence of a big vegetation (4x1cm) on the pulmonary valve that caused moderate pulmonary insufficiency (images 3, 4). Neither tricuspid nor left side valves were involved. Biventricular function was conserved and hyperdynamic. Endocarditis diagnosis was definitive and due to the presence of multiple right embolisms and the big size of the vegetation, the patient underwent cardiac surgery. Intra-surgical finding demonstrated a big vegetation of almost 5 cm (image 5) depending of the posterior pulmonary valve that was removed; the posterior valve needed to be repaired. Posterior clinical evolution was correct without complications, completing 17 days of i.v. antibiotics (cloxaciline) before discharge. CONCLUSIONS: Right endocarditis is a rapidly progressive disease due to the fact that staphylococcus are the most frequent microorganisms involved. Valvular destruction and secondary embolic phenomena are the rule. Tricuspid valve is involved most of the times being the isolated pulmonary valve affection very uncommon.